Formation of the republican budget – realization of the state budget policy - Жунусова, Р. М.; Жусупова, А. К.; Утибаева, Г. Б. (Journal of Economic Research & Business Administration, 2015)
In the article reveals the indicates of the republican budget for 2012-2014 from the view of implementation of republican budget policy are examined. Particular attention is drown to revenues part of the budget, specifically to the growth factors of tax receipts, as well as transfers, which volume is anticipated to significantly higher than in previous years. The comparative analyses of the volume, structure and directions of the budgetary lending is given in the article.